EDUKASI SEPUTAR PENYAKIT TIDAK MENULAR PADA MAHASISWA PROGRAM STUDI ILMU KESEHATAN MASYARAKAT FKIK UNIVERSITAS JAMBI - Mekarisce, Arnild Augina; Ningsih, Vinna Rahayu; Tarawifa, Susan (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2024)
Non-communicable diseases (NCDs) are preventable and their risk factors can be controlled. However, most of the behaviors that are at risk of NCDs are often unaware of it. Based on preliminary studies on 259 students of the Public Health Science Study Program (Prodi IKM), it is known that students have never conducted basic routine examinations at least once a year (16.3%) and students do not know the concept of